Clinical characteristics and survival outcomes of patients with renal cell carcinoma in a Tanzanian cohort - Damian Kisenha; Meshack Brighton; Daniel Kitua; Fransia Arda; Ally Mwanga; Gabriel Mtaturu; Nashivai Kivuyo; Mungeni Misidai; Charles Mkony (African Journal of Urology)
Abstract Background Renal cell carcinoma (RCC) poses a substantial public health challenge globally; however, there is limited information available regarding its clinicopathological characteristics, treatment strategies, and outcomes in Tanzania. The study aimed to describe the clinicopathological profiles and determine survival outcomes of patients with RCC at a quaternary health facility, the highest referral level in Tanzania. Methodology This retrospective cohort study was conducted in January 2024 among patients diagnosed with RCC and treated at the Urology Department of Muhimbili National Hospital. Clinical, demographic, treatment, and survival data were collected from medical records and through consecutive sampling of patients treated between January 1, 2017, and December 31, 2023, by contacting patients or their next of kin. Descriptive statistics were presented as frequencies, percentages, means, and medians. The Chi-square or Fisher's exact test was used to assess associations between predictor variables and survival. A p-value of less than 0.05 was considered statistically significant. Results The study included 70 patients, with a mean age of 54 ± 17 years and a slight male predominance (54.3%). A significant proportion (34.3%) presented with advanced-stage disease (stage IV). The primary treatment modality was nephrectomy (84%), while the rest received non-surgical care. The common histological variants were clear cell (21.4%) and papillary carcinoma (20%). The in-hospital mortality rate was 11.4%, and the 5-year survival rate was 17.1%. Demographic, clinical, and pathological characteristics did not show significant associations with survival outcomes (p > 0.05). Conclusion The study underscores a high mortality rate and the prevalence of advanced-stage RCC at the time of diagnosis, highlighting the urgent need for strategies to enhance early detection and timely intervention to improve survival outcomes.